Ehrenfeucht theories with non-dense powerful digraphs* - Sudoplatov, S.V. (Ye.A.Buketov Karaganda State University Publishing house, 2013)
All known Ehrenfeucht theories are based on powerful digraphs having the density property. In the paper, we construct examples of Ehrenfeucht theories with powerful digraphs having the non-density property, i. e., with covering elements for each vertex of digraph. The construction of required theories is realized by syntactic generic ones allowing to synthesize saturated models based on the class of finite structures with some type add-ins, closed under amalgams.
Тығыз емес үстем орграфты эренфойхт теориялары
Эренфойхтовы теории с неплотными властными орграфами
Keywords: Ehrenfeucht theory; powerful digraph; density property; covering element; syntactic generic construction